Juridical Analysis of Protection of Passengers' Compensation Rights Against Airline Cancellations - Margaretha, Irene Patricia; Mulyadi, Marsel; Gorga, Alexander Kevin; Saly, Jeane Neltje (CV. Rayyan Dwi Bharata, 2023)
Flight cancellations by airlines in Indonesia are a serious concern for passengers who often experience inconvenience and loss due to this situation. This journal aims to analyze the protection of the right to compensation for passengers who experience flight cancellations in Indonesia, as well as present a legal review regarding this matter. This study uses an analytical descriptive legal method and is based on existing legal regulations in Indonesia, particularly Law No. 1 of 2009 concerning Aviation. The analysis is carried out through tracing and reviewing laws and regulations, related court decisions, and relevant legal literature. The results of the study show that passengers are entitled to compensation when facing flight cancellations by the airline. The law provides a strong legal basis for the protection of these rights. Article 15 of Law Number 1 of 2009 concerning Aviation expressly states that airline companies are obliged to provide compensation to passengers who experience flight cancellations without clear reasons or without adequate notification.